The strategy of Implemented Limited Face-to-Face Learning Policy in Junior High School During the Covid-19 Pandemic - Novi Rismawati; Ivan Hanafi; Siti Zulaikha Zulaikha (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this study was to describe the strategy of implementing a limited face-to-face learning policy in junior high school during the covid-19 pandemic. The study used qualitative method. This research was conducted at a State Junior High School in Merauke, Papua Province. Participants consisted of 30 people consisting of principals, teachers, and school committees. Data collection techniques using observation, interviews, and documents. Data analysis techniques consist of 1) data collection, 2) data Reduction, 3) data display, and 4) conclusion. The validity of the data were credibility, transferability, dependability, and objectivity (confirmability). The finding shows that there were two main strategy which implemented in limited face-to-face learning policy in the school. It used to make the concepts of communication, the readiness of human resources, and the development of cooperative attitudes. The strategies were standard operational procedures and fragmentation. School made the rule for limited learning process. Standard Operational Procedures that are used as internal school demands to implement policies uniformly in junior high schools. Fragmentation is designed as a form of division of responsibility for implementing limited face-to-face learning policies. It is carried out by taking into account the nature of the policy to be implemented, and the distribution of responsibilities to all policy implementers. The strategy provided the concept of face-to-face learning is limited to meeting the needs of children's growth and development towards educational needs so learning activities must refer to the principles of health, safety, and children's rights.